2013
DOI: 10.1155/2013/263046
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Concomitant Perforated Acute Cholecystitis and Pancreatitis

Abstract: Introduction. Concomitant cholecystitis and gallstone pancreatitis is an infrequent clinical encounter, reported sparsely in the literature. Concurrent acute cholecystitis and pancreatitis complicated by gall bladder perforation has not been reported before. Presentation of Case. We report a 39-year-old female presenting with concomitant cholecystitis and acute pancreatitis, complicated by gallbladder perforation. Discussion. There is much controversy surrounding the timing of cholecystectomy following gallsto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
7
0
1
Order By: Relevance
“…Pancreatic hyper-enzymemias have been found in various other conditions. There are reports of concomitant GB perforation with pancreatitis, however the pancreas was normal in USG, MSCT and even on direct inspection during the laparotomy [5] . In cases of gall bladder perforation, pancreatic hyper-enzymemia may be seen due to the presence of ectopic pancreatic tissue in the gall bladder wall which is not a rare site for ectopic pancreatic tissue [6] .…”
Section: Discussionmentioning
confidence: 92%
“…Pancreatic hyper-enzymemias have been found in various other conditions. There are reports of concomitant GB perforation with pancreatitis, however the pancreas was normal in USG, MSCT and even on direct inspection during the laparotomy [5] . In cases of gall bladder perforation, pancreatic hyper-enzymemia may be seen due to the presence of ectopic pancreatic tissue in the gall bladder wall which is not a rare site for ectopic pancreatic tissue [6] .…”
Section: Discussionmentioning
confidence: 92%
“…It was previously thought that cholecystectomy favourably influences the course of acute pancreatitis when occurred as a concomitant of acute calculous cholecystitis [8, 9]. However, more recent studies have demonstrated that early surgical intervention during the acute inflammatory phase of pancreatitis should be avoided due to high morbidity and mortality associated SIRS [10] as well as pancreatic oedema impairing Calot’s triangle dissection [5].…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis is also a common condition, with annual incidence worldwide of 4.9–73.4 cases per 100 000 people [2], and of these gallstone pancreatitis makes up ~50% of the cases, followed closely by alcohol induced pancreatitis [3]. Although being the two commonest gallstone-related conditions, these cholecystitis and pancreatitis rarely occur concurrently, [4, 5] thus there are only limited reports in the literature. Nevertheless, recent pathological and radiological studies have demonstrated their concomitant occurrence may be much higher than thought to be [4, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Perera et al in 2013 reported a 39-year-old female presenting with concurrent acute cholecystitis and pancreatitis complicated by gall bladder perforation [12]. Page et al in 2008 reported an 18-year-old male presenting with thyroid storm developed immediately after excision of a pituitary TSH-omas [13].…”
Section: Discussionmentioning
confidence: 99%